IMPLEMENTATION OF THE 3-O APPROACH AS AN INNOVATION IN RADIO PROGRAM PRODUCTION - Ismed, Mohammad (Politeknik Negeri Media Kreatif, 2025)
Radio is one of the mass media that evolves along with the development of technology. Innovations are made not only in techniques, but also in broadcast program production. In the past, radio focused more on producing programs for On-Air and Off-Air, now radio has added a platform for producing its programs, that is Online. This innovation was carried out not only to be able to expand opportunities for advertising as a source of income, but also to meet the needs of listeners whose ways of consuming media have also changed along with the development of digital technology. This prompted the current research. The problem raised is how the implementation of On-air, Off-air, and also online approaches can be carried out in a broadcast radio program production. The purpose of this research is to find out and understand the implementation and its influence on the quality of programs on radio media. By using a qualitative approach and descriptive interview and observation methods, it is hoped that this research can describe the process of applying the On-Air, Off-Air, and Online approaches to radio broadcast programs. The results of this study are expected to provide solutions in improving the quality of radio broadcast programs which can provide great opportunities for advertising